Effectiveness Of Nursing Interventions in The Implementation of Primary Health Care Policies: A Systematic Review - Suprapto Suprapto; Yuniharce Kadang (Majalah Kesehatan Indonesia, 2026)
Nursing-led interventions play a critical role in strengthening primary health care (PHC) delivery; however, empirical evidence on their policy-level impact remains fragmented and under-theorized. This review synthesizes quantitative and qualitative findings to evaluate how nursing-driven strategies influence PHC policy implementation outcomes across diverse health system contexts. A systematic search across five major databases and grey literature sources identified eligible studies assessing the effectiveness, feasibility, and contextual determinants of nursing-led interventions using established methodological frameworks. Quantitative analyses demonstrated that these interventions were associated with enhanced measurable policy compliance, improved continuity of care indicators, and greater alignment with PHC implementation targets. Qualitative synthesis further highlighted perceived patient empowerment, the contextual barriers faced by nurses, and the organizational enablers that shape intervention effectiveness. This review provides an integrative synthesis linking nursing-led interventions to PHC policy adherence, offering a novel framework for evaluating community-based policy outcomes. Findings underscore the importance of context-sensitive implementation and highlight opportunities for strengthening PHC systems through nursing leadership.